“Il canto sospeso” di Luigi Nono: un percorso didattico - Somigli, Paolo (Musica Docta, 2015)
This article proposes a series of music education activities centring on Luigi Nono’s Il canto sospeso, one of the most significant compositions of the 20th century. It looks at the work within the historical context that saw its creation, suggesting an approach which relies on the score and on specific references to listening, and in which musical observation goes hand in hand with methodological-didactic suggestions. This proposal also contains inter-disciplinary options and can be expanded to include other musical genres. It is addressed to secondary schools, both at the junior and higher levels.